The proximal experience of gratitude - Layous, Kristin; Sweeny, Kate; Armenta, Christina; Na, Soojung; Choi, Incheol; Lyubomirsky, Sonja (PLOS ONE, 2017)
Although a great deal of research has tested the longitudinal effects of regularly practicing gratitude, much less attention has been paid to the emotional landscape directly following engagement in gratitude exercises. In three studies, we explored the array of discrete emotions people experience after being prompted to express or recall gratitude. In Studies 1 and 2, two different gratitude exercises produced not only greater feelings of gratitude relative to two positive emotion control conditions (i.e., recalling relief), but also higher levels of other socially relevant states like elevation, connectedness, and indebtedness. In a third study, conducted in both the U.S. and S. Korea, we compared a gratitude exercise to another positive emotion elicitation (i.e., recalling a kind act) and to a neutral task, and again found that the gratitude exercise prompted greater gratitude, elevation, indebtedness, and guilt, but no more embarrassment or shame, than the two comparison conditions. Additionally, in all three studies, emodiversity and cluster analyses revealed that gratitude exercises led to the simultaneous experience of both pleasant and unpleasant socially-relevant states. In sum, although it may seem obvious that gratitude exercises would evoke grateful, positive states, a meta-analysis of our three studies revealed that gratitude exercises actually elicit a mixed emotional experience—one that simultaneously leads individuals to feel uplifted and indebted.